2003
DOI: 10.1097/01.asn.0000051726.41601.c0
|View full text |Cite
|
Sign up to set email alerts
|

The Lack of Cyclin Kinase Inhibitor p27Kip1 Ameliorates Progression of Diabetic Nephropathy

Abstract: Abstract. Cyclin kinase inhibitor p27 Kip 1

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
82
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(91 citation statements)
references
References 36 publications
6
82
0
Order By: Relevance
“…Zheng et al (5) found that mesangial cells isolated from kidneys of postmenopausal mice were enlarged and had elevated amounts of p27 kip1 protein expression as assessed by immunochemistry. Other studies (35)(36)(37) also showed that p21 cip1 and p27 kip1 were required for retinoblastoma protein-mediated senescence, demonstrating not only that p21 cip1 and p27 kip1 gene transfer could promote cell senescence but also that antisense p21 cip1 and p27 kip1 had some effects on retarding the progress of cell hypertrophy or senescence. Our results showed that Cx43 knockdown significantly increased p21 cip1 and p27 kip1 expression in GMC, whereas Cx43 gene overexpression decreased p21 cip1 and p27 kip1 protein levels in GMC cultured in high glucose, indicating that Cx43 could control cell proliferation and senescence progression through cell-cycle regulation.…”
Section: Discussionmentioning
confidence: 90%
“…Zheng et al (5) found that mesangial cells isolated from kidneys of postmenopausal mice were enlarged and had elevated amounts of p27 kip1 protein expression as assessed by immunochemistry. Other studies (35)(36)(37) also showed that p21 cip1 and p27 kip1 were required for retinoblastoma protein-mediated senescence, demonstrating not only that p21 cip1 and p27 kip1 gene transfer could promote cell senescence but also that antisense p21 cip1 and p27 kip1 had some effects on retarding the progress of cell hypertrophy or senescence. Our results showed that Cx43 knockdown significantly increased p21 cip1 and p27 kip1 expression in GMC, whereas Cx43 gene overexpression decreased p21 cip1 and p27 kip1 protein levels in GMC cultured in high glucose, indicating that Cx43 could control cell proliferation and senescence progression through cell-cycle regulation.…”
Section: Discussionmentioning
confidence: 90%
“…Furthermore, treatment of BBdp rats, a model of autoimmune diabetes mellitus Type 1, with angiotensin-converting enzyme inhibitors reduced the glomerular expression of p27 Kip1 and this was accompanied by a decrease in renal hypertrophy [20]. In addition, p21 Cip1 -/- [21] and p27 Kip1 -/- [22] mice are protected to some extent of the development of morphological and functional changes of diabetic nephropathy. These studies clearly show a pivotal role for these specific CDK-inhibitors in the development of glomerular hypertrophy of diabetes mellitus.…”
Section: Discussionmentioning
confidence: 96%
“…It has also been reported that MC isolated from p27 Ϫ/Ϫ mice did not undergo cellular hypertrophy under high glucose conditions (25,26). More recently, the significance of p27 in the progression of diabetic nephropathy in vivo has also been established (44). However, the underlying upstream mediators of Ang II-induced MC hypertrophy are not fully identified.…”
Section: Discussionmentioning
confidence: 99%